Cardiac Hemangioma in the Left Ventricular Septum - Ilcheva, Lilly; Cholubek, Magdalena; Loiero, Dominik; Dzemali, Omer (The Thoracic and Cardiovascular Surgeon Reports, 2024)
Background Primary cardiac tumors are an exceedingly rare benign group of tumors that may remain asymptomatic for a prolonged duration or could lead to significant clinical events.Case Presentation A 64-year-old female patient underwent echocardiography prior to elective knee surgery due to the presence of palpitations and dyspnea. This revealed the existence of a mass located on the left side of the interventricular septum, which was resected successfully.Conclusion Surgical resection represents the primary therapeutic approach for the management of cardiac hemangiomas. Failure to perform timely resection may elevate the risk of developing total atrioventricular block and experiencing sudden death.
Keywords: cardiac; tumor; cardiac hemangioma